2016
DOI: 10.1186/s40634-016-0056-2
|View full text |Cite
|
Sign up to set email alerts
|

Biomechanical and histological comparison between the cryopreserved and the lyophilized Gracilis tendon allograft for MPFL reconstruction, a cadaveric experimental study

Abstract: BackgroundMedial patellofemoral ligament (MPFL) is the main restrictor of lateral shifting of the patella, contributing by 60 % in the first 20° flexion of the knee. MPFL reconstruction has been performed in order to restore the stability of the patella with good results.Lyophilized Gracilis tendon allograft (LGA) compared to Cryopreserved Gracilis tendon allograft (CGA) has a lower cost, does not require to maintain cooling chain or preparation. The purpose of this study is to compare the histological and bio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 20 publications
0
10
0
Order By: Relevance
“…McNeilan et al 22 showed in a recent publication that there is no biomechanical difference in the use of auto or allograft, justified in the low resistance (217 N) of the native MPFL and it would be enough to have a graft 240 mm long and 5 to 6 mm diameter for proper reconstruction. Regarding the use of cryopreserved or lyophilized allograft, Negrín et al 23 in 2016 demonstrated in a study, conducted on 36 swine knees, that there would be no difference in maximum tensile resistance, elongation, area of failure, graft strength or histology.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…McNeilan et al 22 showed in a recent publication that there is no biomechanical difference in the use of auto or allograft, justified in the low resistance (217 N) of the native MPFL and it would be enough to have a graft 240 mm long and 5 to 6 mm diameter for proper reconstruction. Regarding the use of cryopreserved or lyophilized allograft, Negrín et al 23 in 2016 demonstrated in a study, conducted on 36 swine knees, that there would be no difference in maximum tensile resistance, elongation, area of failure, graft strength or histology.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the use of cryopreserved or lyophilized allograft, Negrín et al. 23 in 2016 demonstrated in a study, conducted on 36 swine knees, that there would be no difference in maximum tensile resistance, elongation, area of failure, graft strength or histology.…”
Section: Discussionmentioning
confidence: 99%
“…The porcine patella was chosen because it has also been well established in similar biomechanical models. 11 , 15 , 22 In this model, we also used tissue that was not irradiated or sterilized in any way. It has been demonstrated that higher doses of irradiation can affect biomechanical properties of soft-tissue allografts, and even low-dose irradiation may affect the stiffness.…”
Section: Discussionmentioning
confidence: 99%
“…Porcine patellae were used as this is an established and described model of MPFL reconstruction. 11 , 15 , 22 The tendons were not sterilized using irradiation or other techniques. The patellae and tendons were stored at −20°C until 5 hours before testing.…”
Section: Methodsmentioning
confidence: 99%
“…2). Moreover, the presence of a crimp period in paraffin‐embedded tissue sections was also confirmed by using hematoxylin/eosin staining, analyzing the tendon sections by light microscopy 6,44 , and using van Gieson staining 45 . Furthermore, Franchi et al 46 .…”
Section: Introductionmentioning
confidence: 92%